SOLUTION MECHANISMS OF PHOSPHORUS IN QUENCHED HYDROUS AND ANHYDROUS GRANITIC GLASS AS A FUNCTION OF PERALUMINOSITY - Mysen B.O.; Holtz F.; Pichavant M.; Beny J.M.; Montel J.M. (My University, 1997)
Solution mechanisms of P in metaluminous to peraluminous quenched, hydrous (#9 wt% H2O) and anhydrous glasses in the system CaO-Na2O-K2O-Al2O3-SiO2-P2O5 have been examined with microRaman spectroscopy. The principal aim was to examine relative stability of phosphate complexes as a function of bulk chemical composition. Increasing peraluminosity was accomplished by increasing Al3_ and Ca2+ proportions with constant SiO2 content. The molar ratio Al2O3/(CaO + Na2O + K2O) (A/CNK) ranged from 1 (metaluminous) to #1.3 (peraluminous).In all compositions P5+ is bonded to Al3+ to form A1PO4 complexes. The principal solution mechanism is one where depolymerized species (Q3), involving Al3+ both within and outside the aluminosilicate network, interact with P to form the A1PO4 complex together with Q4 species. The mechanism does not involve alkali metals or alkaline earths. In anhydrous compositions, the spectra are interpreted to suggest Si-O-P cross-linking in the structure. In hydrous compositions, evidence for Si-O-P bonding is less evident. In such glasses, there is, however, possible spectroscopic evidence for Si-OH bonding and possibly P-OH bonding resulting from breakage of cross-linking Si-O-P bonds existing in the anhydrous glasses. Therefore, the water content of peraluminous aluminosilicage melts is likely to affect the solubility behavior of P, and conversely, the solubility behavior of H2O is affected by P in such melts.